2003
DOI: 10.1038/sj.leu.2402913
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells loaded with apoptotic tumour cells induce a stronger T-cell response than dendritic cell–tumour hybrids in B-CLL

Abstract: Dendritic cells (DC) are professional (specialised) antigenpresenting cells that can capture antigen from apoptotic tumour cells and induce MHC class I-and II-restricted responses. Also, DC fused with tumour cells may be effective for immune response induction. Both cell preparations may be considered as vaccine candidates in a therapeutic approach. We examined autologous T-cell activation by DC that had endocytosed leukaemic B-cell apoptotic bodies (Apo-DC) and compared it to the T-cell stimulatory capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 29 publications
(21 reference statements)
1
47
0
Order By: Relevance
“…our previous experiment had shown that monocyte-derived dendritic cells from patients with breast cancer were capable to elicit mixed leuleocyte reaction (MLR) in vitro (data not shown), in the present study we demonstrated that tumor lysate pulsed DC could generate T cell proliferative response in vitro, proliferation induction by antigen loaded DCs, revealed that tumor lysate preparation would contain immunogenic epitopes that processed and presented by DC properly. In accordance to previous studies we showed that proliferative responses varied from patient to patient which expressed as different stimulation indexes [32], furthermore, the responses were increased by increasing the ratio of DC: T cells. Collectively, our findings as well as the results of other studies suggests that breast tumor antigens in the forms of tumor cell lysate or tumor-dendritic cells hybrid could elicit autologous T cell proliferative responses in vitro [25].…”
Section: Discussionsupporting
confidence: 70%
“…our previous experiment had shown that monocyte-derived dendritic cells from patients with breast cancer were capable to elicit mixed leuleocyte reaction (MLR) in vitro (data not shown), in the present study we demonstrated that tumor lysate pulsed DC could generate T cell proliferative response in vitro, proliferation induction by antigen loaded DCs, revealed that tumor lysate preparation would contain immunogenic epitopes that processed and presented by DC properly. In accordance to previous studies we showed that proliferative responses varied from patient to patient which expressed as different stimulation indexes [32], furthermore, the responses were increased by increasing the ratio of DC: T cells. Collectively, our findings as well as the results of other studies suggests that breast tumor antigens in the forms of tumor cell lysate or tumor-dendritic cells hybrid could elicit autologous T cell proliferative responses in vitro [25].…”
Section: Discussionsupporting
confidence: 70%
“…It was reported previously that apoptotic bodies were favorable for DC presenting tumor antigens. [48][49][50][51][52] Therefore, apoptosis of the CD154-tranfected cells after administration in vivo may even be favorable for immunotherapy. Human clinical studies are underway to determine the effectiveness of CD154-transfected B-CLL cells in producing in vivo immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…6 Briefly, CD14 þ monocytes were immunomagnetically enriched from PBMC obtained by Ficoll separation of peripheral blood. The starting purity of the monocytes was 93.372% (mean7s.e.m.)…”
Section: Generation Of Dendritic Cellsmentioning
confidence: 99%
“…5 Large numbers of DC required for clinical therapy can be generated in vitro by culturing peripheral blood monocytes in the presence of GM-CSF and IL-4. 6 A critical issue in optimizing DC vaccines is choosing the proper source and subtype of DC as well as the source of tumor antigen(s). Clinical vaccination trials for patients with malignant melanoma have demonstrated that vaccinating against a single antigen can induce tumor-specific CTLs but carries the risk of promoting tumor antigen escape variants.…”
Section: Introductionmentioning
confidence: 99%